Digitalization of Restaurant Services: Android-Based Menu Ordering Application - Setya Ningtyas, Ayu; Aminah, Siti; Tirtana, Arif; Nengsih, Titin Agustin (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2025)
Utilization of mobile application technology which can be one of the considerations for presenting information in various business actors because of its flexible and easy nature. One of them is the Betawi Babeh Sadeli Restaurant which is currently still implementing a manual ordering method, the waiter records the menu to be ordered, then delivers the order to the kitchen which requires a lot of time and effort. From these problems, the authors provide a solution for designing a food menu ordering application for Android-based mobile devices with the waterfall method. This study aims to design a real-time food menu ordering system for Android-based mobile devices using the waterfall method. The developed application streamlines the ordering process at the Betawi Babeh Sadeli Restaurant. Functionality testing results indicate that 92% of the application features functioned correctly, demonstrating its effectiveness and reliability.